Changes in fall armyworm (Lepidoptera: Noctuidae) fitneá over five generations after larval feeding on resistant tropical landrace sorghum - Lopez, J.=700 1 Pitre, H.N.; Meckenstock, D.H.
(Es, En)
Ilus., 15 ref.
Keywords: SORGHUM BICOLOR; SPODOPTERA FRUGIPERDA; INSECTA; RESISTENCIA A LAS PLAGAS; HONDURAS